PROTECTIVE EFFICACY OF PERTACTIN CONTAINING ACELLULAR DPT VACCINES - M.V. Fesenko; L.S. Namazova ("Paediatrician" Publishers LLC, 2008)
Pertussis vaccination with the use of DPT vaccines is a necessary condition for fighting the infection called bordetella pertussis. At the same time, it is known that the use of whole cellular DPT vaccines is accompanied with high incidence of side effects and serious neurological complications, and, as a result, reasonable refuse from injections by the population. Creation of less reactogenic, acellular vaccines would not only permit to decrease the incidence of side effects, but also increase the efficiency of pertussis vaccination. Maximum protective effect is achieved by using threebcomponent vaccines ( 80%), containng pertactin - outer membrane protein b. pertussis. the absence of this antigen in twobcomponent DPT vaccines predetermines their significantly lower efficacy. Key words: children, pertussis, acellular DPT vaccines, pertactin.